Identification of the wave speed and the second viscosity in cavitating flow with 2D RANS computations - Part II. (November 2015) - Alligné, S; Decaix, J; Nicolet, C; Avellan, F; Münch, C
Abstract: The 1D modelling of cavitation vortex rope dynamics in Francis turbine draft tube is decisive for prediction of pressure fluctuations in the system. However, models are defined with parameters which values must be quantified either experimentally or numerically. In this paper a methodology based on CFD simulations is setup to identify these parameters by exciting the flow through outlet boundary condition. A simplified test case is considered to assess if 1D cavitation model parameters can be identified from CFD simulations. It is shown that a low wave speed and a second viscosity due to the cavitating flow can be identified.